Analisis Kemampuan Pemecahan Masalah Matematis pada Pembelajaran Matematika Dilihat dari Tipe Kepribadian Peserta Didik - Muhammad Arya Satya; Agustiany Dumeva Putri; Harisman Nizar (SJME (Supremum Journal of Mathematics Education), 2022)
This study aims to analyze mathematical problem solving abilities in mathematics learning based on the personality types of students. The research method used in this study is a descriptive method with a qualitative approach. The subjects of this study were 6 students of SMP Tunas Teladan Palembang in the odd semester of the 2021/2022 academic year. Subjects were taken using purposive sampling technique, based on the personality type of the students. Data analysis in this research is qualitative data analysis which consists of data reduction, data presentation and conclusion drawing. From this study, it was concluded that: (1) students with extroverted personality type were able to meet problem solving indicators at the stage of understanding problems, planning and solving problems, but did not meet indicators at the re-examining stage (2) students with introverted personality types were able to fulfill all problem solving indicators at the stage of understanding the problem, making plans, solving problems and checking again.